Influence of sex on survival, neurologic outcomes, and neurodiagnostic testing after out-of-hospital cardiac arrest. (October 2021) - Vogelsong, Melissa A.; May, Teresa; Agarwal, Sachin; Cronberg, Tobias; Dankiewicz, Josef; Dupont, Allison; Friberg, Hans; Hand, Robert; McPherson, John; Mlynash, Michael; Mooney, Michael; Nielsen, Niklas; et al.
Abstract: Aim: Previous studies evaluating the relationship between sex and post-resuscitation care and outcomes following out-of-hospital cardiac arrest (OHCA) are conflicting. We investigated the association between sex and outcomes as well as neurodiagnostic testing in a prospective multicenter international registry of patients admitted to intensive care units following OHCA. Methods: OHCA survivors enrolled in the International Cardiac Arrest Registry (INTCAR) from 2012 to 2017 were included. We assessed the independent association between sex and survival to hospital discharge, good neurologic outcome (Cerebral Performance Category 1 or 2), neurodiagnostic testing, and withdrawal of life-sustaining therapy (WLST). Results: Of 2407 eligible patients, 809 (33.6%) were women. Baseline characteristics differed by sex, with less bystander CPR and initial shockable rhythms among women. Women were less likely to survive to hospital discharge, however significance abated following adjusted analysis (30.1% vs 42.7%, adjusted OR 0.85, 95% CI 0.67–1.08). Women were less likely to have good neurologic outcome at discharge (21.4% vs 34.0%, adjusted OR 0.74, 95% CI 0.57–0.96) and at six months post-arrest (16.7% vs 29.4%, adjusted OR 0.73, 95% CI 0.54–0.98) that persisted after adjustment. Neuroimaging (75.5% vs 74.3%, p = 0.54) and other neurophysiologic testing (78.8% vs 78.6%, p = 0.91) was similar across sex. Women were more likely to undergo WLST (55.6% vs 42.8%, adjusted OR 1.35, 95% CI 1.09–1.66). Conclusions: Women with cardiac arrest have lower odds of good neurologic outcomes and higher odds of WLST, despite comparable rates of neurodiagnostic testing and after controlling for baseline differences in clinical characteristics and cardiac arrest features.